Elusive Gold and Uncertainty in Artisanal and Small-Scale Mining - Frohn Pedersen, Anna (Ethnos, 2023)
Artisanal and small-scale mining is one of the main non-farm rural livelihoods in the global south. Mostly, it is done with no geological data available to locate the minerals. This is also the case in Geita, the main gold mining region of Tanzania, to where men and women migrate hoping to make a living. Drawing on the concept of ‘geosocialities’ a term which captures the manifold entanglements of social life and geologies, I approach artisanal and small-scale mining as a way of navigating in and with elusive geologies, and I show how geo-uncertainty shapes lives and landscapes in northern Tanzania. I highlight how ‘not yet’ and potentially absent minerals also partake in world-making. A geosocial focus on the ‘not yet’ minerals, I suggest, can help us understand geo-uncertainty in the extractive industries as embodied practices that create futures of hope, precarity and environmental degradation.
Created from Fastlane, Scopus look-up
Keywords: Artisanal and small-scale mining; geosocialities; gold; Tanzania; uncertainty